Recurrent Primary Intrasellar Paraganglioma - Schueth, Elizabeth A.; Martinez, Daniel C.; Kulwin, Charles G.; Bonnin, Jose M.; Payner, Troy D.; Ting, Jonathan Y. (Case Reports in Otolaryngology, 2020)
We describe a case of an 81-year-old male presenting with bitemporal visual field defects and blurry vision in the right eye. The patient was found to have a recurrent primary paraganglioma in the sellar and suprasellar region requiring a repeat transsphenoidal endoscopic resection. Immunohistochemical examination confirmed paraganglioma with the classic zellballen appearance which stained positive for chromogranin, synaptophysin, and S-100 in the periphery. Paragangliomas (PGLs) in the sella turcica are a rare entity; only 19 cases have ever been reported in the literature. PGLs in the sellar region are often misdiagnosed or diagnosed in a delayed fashion. Earlier diagnosis of this locally aggressive tumor and meticulous debulking can prevent morbidity secondary to the tumor’s compressive effects. This report highlights the effectiveness of surgical interventions in treatment of paragangliomas. More research is still needed to determine the need for adjuvant therapies such as radiation.